Levels of intrinsic coagulation factors and the risk of myocardial infarction among men: Opposite and synergistic effects of factors XI and XII - Doggen, Carine J M; Rosendaal, Frits R; Meijers, Joost C M (Blood, 2006)
The role of the intrinsic coagulation system on the risk of myocardial infarction is unclear. In the Study of Myocardial Infarctions Leiden (SMILE) that included 560 men younger than age 70 with a first myocardial infarction and 646 control subjects, we investigated the risk of myocardial infarction for levels of factor XI (factor XIc) and factor XII (factor XIIc). Furthermore, the risks for factor VIII activity (factor VIIIc) and factor IX activity (factor IXc) were assessed. Factor XIc was 113.0% in patients compared with 109.8% in control subjects (difference, 3.2%; 95% CI, 1.1%-5.4%). The risk of myocardial infarction adjusted for age for men in the highest quintile compared with those in the lowest quintile was 1.8-fold increased (ORadj, 1.8; 95% CI, 1.2-2.7). In contrast, factor XIIc among patients with myocardial infarction was lower than in control subjects, respectively, 93.0% and 98.6% (difference, 5.6%; 95% CI, 3.3%-7.9%). The odds ratio of myocardial infarction for men in the highest quintile versus those in the lowest quintile was 0.4 (ORadj, 0.4; 95% CI, 0.2-0.5). The highest risk was found among men with both high factor XIc and low factor XIIc (analyses in tertiles: ORadj, 6.4; 95% CI, 2.2-18.0). Factor VIIIc increased the risk of myocardial infarction although not dose dependently. Factor IXc increased the risk; odds ratio of myocardial infarction for men in the highest quintile versus those in the lowest quintile was 3.2 (ORadj, 3.2; 95% CI, 2.0-5.1). Thus, factors XIc and XIIc have opposite and synergistic effects on the risk of myocardial infarction in men; factor VIIIc and factor IXc increase the risk.